2017
DOI: 10.1186/s12936-017-1698-y
|View full text |Cite
|
Sign up to set email alerts
|

Artemether-lumefantrine and liver enzyme abnormalities in non-severe Plasmodium falciparum malaria in returned travellers: a retrospective comparative study with quinine-doxycycline in a Portuguese centre

Abstract: Background Artemisinin-based therapy is the current standard treatment for non-severe malaria due to Plasmodium falciparum. The potential for asymptomatic liver toxicity of this therapy and its implication in clinical practice is currently unknown. The aim of this study is to assess the hepatic function in patients treated with a standard three-day artemisinin-based regimen and to compare it with the quinine-doxycycline regimen.MethodsRetrospective and comparative study of returned adult travellers admitted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…This study specifically advocates the relevance in relation to potential clinical implications in uncomplicated disease, which constitutes the vast majority of clinical malaria cases. This study highlights that LFT abnormalities can be severe (up to >20 xULN), but are apparently fully reversible upon parasitological cure, corroborating previous reports [ [25] , [26] , [27] ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study specifically advocates the relevance in relation to potential clinical implications in uncomplicated disease, which constitutes the vast majority of clinical malaria cases. This study highlights that LFT abnormalities can be severe (up to >20 xULN), but are apparently fully reversible upon parasitological cure, corroborating previous reports [ [25] , [26] , [27] ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings reflect a need to understand and reassess LFT abnormalities in malaria. This will have significant impact on clinical decision-making and in drug development, where they are often interpreted as drug-induced liver injury, particularly in malaria drug studies [ 27 , 42 ]. For example, drug-related serious adverse events in a recent multicentre trial comparing pyronaridine–artesunate or dihydroartemisinin–piperaquine versus current first-line therapies for uncomplicated malaria were associated mainly with increased liver enzymes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other studies associating artemisinin-containing treatment regimens, and presumably more rapid parasite clearance, with LFT elevations. 28 Plasmodium falciparum infection was associated with a higher frequency of abnormal LFTs overall. However, when the three time period groups were compared, the proportion of P. falciparum cases compared with P. vivax cases was only different between the normal and early transaminase elevation groups.…”
Section: Discussionmentioning
confidence: 90%
“…Peaks in transaminase levels after treatment have also been recently reported; these could represent a distinct type of malaria-associated liver injury. 28 31 In a small retrospective comparative European study, asymptomatic transaminase elevation was observed in returned travelers hospitalized for malaria after treatment with the artemisinin-based combination therapy artemether–lumefantrine. The authors postulated that the rapid parasiticidal effect of the antimalarial treatment may promote accelerated hepatic heme loading and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation